2000
DOI: 10.1164/ajrccm.161.3.9901042
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Alveolar Type I Cell–Specific Biochemical Marker of Human Acute Lung Injury

Abstract: Currently there is no recognized biochemical or molecular marker for human parenchymal lung injury analogous to markers for acute myocardial injury. Injury to the alveolar epithelial barrier is of central importance in the pathogenesis of and recovery from acute lung injury. In animal models, an alveolar type I cell-specific protein, RTI(40), has been shown to be an accurate marker of alveolar epithelial damage. We now report that HTI(56), a novel apical plasma membrane protein specific to the human type I cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
2

Year Published

2001
2001
2007
2007

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 32 publications
0
24
0
2
Order By: Relevance
“…However, HTI 56 , a human ATI-cell-specific protein, has been measured in oedema fluid and plasma from patients with established ARDS. The concentration of HTI 56 was significantly elevated in both oedema fluid and plasma from patients with ARDS in comparison to those from hydrostatic pulmonary oedema patients [100]. These data suggest that ATI-cell-specific membrane proteins may be sensitive markers of alveolar epithelial injury in patients with, and at-risk of, ALI or ARDS.…”
Section: Expression Of Alveolar Epithelial Type I Cell-selective Protmentioning
confidence: 72%
“…However, HTI 56 , a human ATI-cell-specific protein, has been measured in oedema fluid and plasma from patients with established ARDS. The concentration of HTI 56 was significantly elevated in both oedema fluid and plasma from patients with ARDS in comparison to those from hydrostatic pulmonary oedema patients [100]. These data suggest that ATI-cell-specific membrane proteins may be sensitive markers of alveolar epithelial injury in patients with, and at-risk of, ALI or ARDS.…”
Section: Expression Of Alveolar Epithelial Type I Cell-selective Protmentioning
confidence: 72%
“…Researchers have sought a specific marker of lung injury in the alveolar lining fluid that may aid in the diagnosis or prognosis of the disease (10,25,26). Conner et al (10) have reported that patients with acute respiratory distress syndrome have increased levels of sICAM-1 in lung edema fluid compared with serum.…”
Section: Discussionmentioning
confidence: 99%
“…Newman and colleagues (15,42) reported that HTI56 is another alveolar type I cell specific protein that can be used as a marker in human ALI. However, in that study, the quantification of HTI56 was based on the standard curve generated by only partially purified HTI56, which was purified from normal lung tissue obtained from a resected lung specimen (15). In addition, HTI56 is poorly soluble in aqueous media and therefore difficult to assay.…”
Section: Rage As a Marker Of Alveolar Type I Epithelial Cell Injury Imentioning
confidence: 99%
“…In this context, some alveolar type I epithelial cell proteins have been demonstrated to be markers of the severity of lung injury in animal and human studies (14,15). Because of the new evidence regarding high concentrations of RAGE in the lung apparently localized primarily to alveolar epithelial type I cells (1,2), we hypothesized that RAGE may be a useful biochemical marker of alveolar type I epithelial cell injury in ALI and ARDS.…”
mentioning
confidence: 99%